2016
DOI: 10.1097/anc.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Care in North American Pediatric Cardiac Intensive Care Units

Abstract: Background Developmental care practices across pediatric cardiac intensive care units (CICUs) have not previously been described. Purpose To characterize current developmental care practices in North American CICUs. Methods A 47-item online survey of developmental care practices was developed and sent to 35 dedicated pediatric CICUs. Staff members who were knowledgeable about developmental care practices in the CICU completed the survey. Findings/Results Completed surveys were received from 28 CICUs (80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 22 publications
(26 reference statements)
1
87
0
1
Order By: Relevance
“…12,35 Research demonstrates that individualized developmental care and other rehabilitative and developmental therapies initiated early in the hospital stay improve long-term outcomes for hospitalized infants. 12,35 Research demonstrates that individualized developmental care and other rehabilitative and developmental therapies initiated early in the hospital stay improve long-term outcomes for hospitalized infants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12,35 Research demonstrates that individualized developmental care and other rehabilitative and developmental therapies initiated early in the hospital stay improve long-term outcomes for hospitalized infants. 12,35 Research demonstrates that individualized developmental care and other rehabilitative and developmental therapies initiated early in the hospital stay improve long-term outcomes for hospitalized infants.…”
Section: Discussionmentioning
confidence: 99%
“…12,35 Research demonstrates that individualized developmental care and other rehabilitative and developmental therapies initiated early in the hospital stay improve long-term outcomes for hospitalized infants. 12 As reported in this study, our assessment identified areas of developmental vulnerabilities at the time of discharge indicating that delays were already notable and the infants were in need of therapeutic services. 12 As reported in this study, our assessment identified areas of developmental vulnerabilities at the time of discharge indicating that delays were already notable and the infants were in need of therapeutic services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last five years, four papers have emerged in the scientific literature calling for a paradigm shift for PCICUs to strategically incorporate developmental care practices [8, 10, 69, 70]. This study provides further evidence that developmental care would benefit the patient-family experience and improve outcomes, specifically to reduce maternal stress.…”
Section: Discussionmentioning
confidence: 86%